A Tacit Monetary Policy of the Gulf Countries: Is There a Remittances Channel? - Ali Termos; Ismail H. Genc; George S Naufal (Institute for the Study of Labor (IZA), 2015)
The strong economic ties between the GCC economies and the U.S. are manifested in three ways: currency peg, coupling of monetary policy, and the adoption of the U.S. dollar as the trading currency for oil. This paper examines how these dynamics result in a misalignment of the U.S. monetary policy with the business cycles of the GCC economies. The study shows how the staggering amount of remittances outflow of the GCC economies plays a stabilizing role as a tacit monetary policy tool. Incorporating remittances in the money demand equation results in a more robust model than otherwise. We further find that the effect of the Federal Funds rate on money demand in these countries diminishes in significance during the period of oil boom between 2002 and 2009. However, the transmission effect of the recession periods in the U.S. into the demand for money in the GCC countries is not statistically significant.
Keywords: F24; N15; 330; remittances; inflation; monetary policy; GCC